Pengaruh Edukasi Pasar Modal, Ekspektasi Return, dan Persepsi Risiko Terhadap Minat Investasi Mahasiswa Pada Instrumen Pasar Modal - Nabila Febriyana; Hwihanus Hwihanus (GEMILANG: Jurnal Manajemen dan Akuntansi, 2024)
This research aims to explore the influence of capital market education, return expectations, and risk perceptions on students' investment interest in capital market instruments. The aim of this research is to understand the factors that influence students' investment interest. Data collection was carried out directly by distributing questionnaires to 96 respondents, with a sampling method using purposive sampling and the criteria for respondents being active students at the relevant university. The analytical tool used in this research is SmartPLS software version 4. The research results show that Capital Market Education has a positive, although not significant, impact on students' Investment Interest in capital market instruments (H1); Return Expectations have a positive and significant impact on students' Investment Interest in capital market instruments (H2); Risk Perception has a negative but not significant impact on students' Investment Interest in capital market instruments (H3).